The elements of logic - Barker, Stephen F. (MCGraw - Hill, 2003)
This classic, concise introductory logic text is designed for courses that cover both formal and informal logic. The text covers a broad, traditional range of topics and includes a large number of exercises which pointedly illustrate logical principles. Answers to selected exercises are included in the study guide.